Flypaper Effect pada Dana Alokasi Umum dan Pendapatan Asli Daerah terhadap Belanja Daerah Kabupaten/Kota di Provinsi Sulawesi Tengah Tahun 2014-2022 - bu abu, Rr Dian hardika pratiwi (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2024)
The purpose of this study is to analyze the Flypaper Effect on regional expenditures in regencies/cities in Central Sulawesi Province during the 2014–2022 period, with an emphasis on General Allocation Funds (DAU) and Local Own-Source Revenue (PAD). The data source used in this study consists of annual APBD realization reports for all regencies/cities in Central Sulawesi Province, obtained from the website of the Directorate General of Fiscal Balance (DJPK). This study involves all regencies/cities in Central Sulawesi Province from 2014 to 2022. The data analysis technique used in this study is Panel Data Regression with E-Views software. The partial test results indicate that DAU has a positive and significant effect on Regional Expenditures with a coefficient value of 0.797, while PAD also has a positive and significant effect with a coefficient value of 0.321. A Flypaper Effect occurs in the DAU and PAD on regional expenditures of regencies/cities in Central Sulawesi Province during the 2014–2022 period based on the partial analysis results, which show that the DAU coefficient value is greater than that of PAD. This means that the higher the General Allocation Fund revenue, the greater the increase in Regional Expenditures. Similarly, the higher the Local Own-Source Revenue, the greater the increase in Regional Expenditures. Keywords: General Allocation Fund, Local Own-Source Revenue, Regional Expenditures,Flypaper effect